International economics and trade liberalisation : challenges to muslim countries - Nik Mustapha Nik Hassan; Mazilan Musa; Azrina Sobian; International Conference "International Economics and Trade Liberalisation" (2000 : Kuala Lumpur, Malaysia) (Kuala Lumpur : IKIM, 2004)
36